Serum levels of the IgA isotype switch factor TGF‐β1 are elevated in patients with COVID‐19. Issue 13 (21st May 2021) - Wang, Er‐yi; Chen, Hao; Sun, Bao‐qing; Wang, Hui; Qu, Hui‐Qi; Liu, Yichuan; Sun, Xi‐zhuo; Qu, Jingchun; Fang, Zhang‐fu; Tian, Lifeng; Zeng, Yi‐feng; Huang, Shau‐Ku; et al.
Abstract : We previously observed enhanced immunoglobulin A (IgA) responses in severe COVID‐19, which might confer damaging effects. Given the important role of IgA in immune and inflammatory responses, the aim of this study was to investigate the dynamic response of the IgA isotype switch factor TGF‐β1 in COVID‐19 patients. We observed, in a total of 153 COVID‐19 patients, that the serum levels of TGF‐β1 were increased significantly at the early and middle stages of COVID‐19, and correlated with the levels of SARS‐CoV‐2‐specific IgA, as well as with the APACHE II score in patients with severe disease. In view of the genetic association of the TGF‐β1 activator THBS3 with severe COVID‐19 identified by the COVID‐19 Host Genetics Initiative, this study suggests TGF‐β1 may play a key role in COVID‐19. Abstract :